Peningkatan Prestasi Belajar IPA Siswa Pada Model Pembelajaran Learning Cycle Dengan Materi Energi dan Perubahannya - Harefa, Darmawan (Fakultas Bahasa dan Sains, Universitas Wijaya Kusuma Surabaya, 2020)
The purpose of this research to find out the improvement students' science learning achievement in the Learning Cycle learning model on energy material and its changes. This type of research is quantitative research with experimental methods. Based on the research results obtained: (1) the average value on the initial test in the experimental class was 70 while the average value of the initial test in the control class was 69.86. (2) The average value of the final test in the experimental class was 84.22, while the average value of the final test in the control class was 73.39. (3) Based on the calculation of the hypothesis test obtained thitung = 3,746> ttable = 1,667. This shows the value of t> t table. Because the value of t> t table then Ha is accepted and Ho rejected at significant level of 5%. So it can be concluded that the increase in science learning achievement of students in the Learning Cycle learning model has positive effect on student achievement in energy material and its changes in Class VI of Lagundri Country. Researcher's suggestion: It is expected that every science subject teacher applies the Learning Cycle learning model to improve student learning achievement.